Fluid Pressure‐Triggered Foreshock Sequence of the 2008 Mogul Earthquake Sequence: Insights From Stress Inversion and Numerical Modeling. Issue 4 (5th April 2019) - Jansen, G.; Ruhl, C. J.; Miller, S. A.
Abstract: In Mogul west of Reno, Nevada, USA, in late February 2008 an earthquake sequence occurred that culminated in a magnitude 4.9 mainshock after a foreshock‐rich period lasting approximately 2 months on previously unidentified fault structures. In this article, we show that the foreshock sequence may have been driven by a fluid pressure intrusion. We use 1, 082 previously calculated earthquake focal mechanisms to infer the local stress field as well as 1, 408 relocated foreshock events to determine the required excess fluid pressure field in the source region of the Mogul earthquake sequence to trigger these events. A model of nonlinear pore pressure diffusion is used to model the fluid flow in a highly fractured subsurface. We find a strong correlation between high fluid pressure fronts and foreshock hypocenters, suggesting a natural fluid‐driven earthquake sequence. Key Points: Stress inversion and overpressure estimates are well suited to evaluate the feasibility of fluid pressure triggering A strong correlation between high fluid pressure fronts and foreshock hypocenters suggests a natural fluid-driven earthquake sequence The lack of dominant upward migration of seismicity does not exclude fluid pressure as driving mechanism